On the evolution of market institutions: the platform design paradox - Carlos Alós-Ferrer; Georg Kirchsteiger; Markus Walzl (Center for Economic Studies and ifo Institute (CESifo), 2007)
We study competition among market designers who create new trading platforms, when boundedly rational traders learn to select among them. We ask whether efficient platforms, leading to market - clearing trading outcomes, will dominate the market in the long run. If several market designers are competing, we find that traders learn to select non-market clearing platforms with prices systematically above the market-clearing level, provided at least one such platform is introduced by a market designer. This in turn leads market designers to introduce non-market clearing platforms. Hence platform competition induces non-competitive market outcomes.
Keywords: C72; D4; D83; L1; 330; E-Business; Lieferanten-Kunden-Beziehung; Marktmechanismus; Institutioneller Wettbewerb; Markteffizienz; Theorie